Incidental finding of multiple well‐differentiated papillary mesotheliomas in peritoneum. Issue 4 (14th January 2016) - Jakobsen, Mark; Engvad, Birte; Jensen, Thor; Marcussen, Niels
Abstract : We present a case of multiple well‐differentiated papillary mesotheliomas (WDPM) in the peritoneum found incidentally in a 63‐year‐old man with urothelial carcinoma of the bladder. When multiple tumors are seen, malignant mesothelioma should be excluded by histopathological examination as this may have a similar focal appearance to WDPM. True stromal invasion is by far the most reliable criterion of mesothelial malignancy. In doubtful cases, a conservative diagnostic approach has been recommended. Compared to malignant mesotheliomas, WDPMs are rare and have a relatively indolent clinical course with a good prognosis. Great care is needed when diagnosing mesothelial proliferations, given the crucial nature of a benign vs malignant diagnosis. No standardized treatment has yet been established.